TRAUMATIC EXPERIENCES IN WILLIAM FAULKNER’S THE SOUND AND THE FURY - Nadia Putri Nazara; Pioro Benevolent Lariesto; Anselmus Chartino Ade (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study aims to analyze the traumatic experiences of the main character, Quentin Compson, in The Sound and the Fury by William Faulkner using a psychoanalytic approach developed by Sigmund Freud, specifically the concepts of the id, ego, and superego. This study also focuses on identifying the types of trauma faced by Quentin and studying how conflicts within his personality structure impact his mental state. The method used is descriptive qualitative. Data collection was conducted through several steps, namely in-depth reading, marking relevant quotes, studying supporting theories, and filtering the data to select the most appropriate textual evidence. Data analysis used the Miles and Huberman framework, which includes data reduction, data presentation, and drawing conclusions and verification based on Freud's psychoanalytic theory. The results of the study indicate that Quentin experienced six interrelated types of trauma: moral, existential, relational, family, identity, and social trauma. These traumas are reflected through the stream-of-conciousness narrative style and furthermore reinforced by the use of symbols the pocket watch, river, and forest. The chaos between id drives, superego pressures, and the failure of the ego as a mediator leads to Quentin's mental breakdown.